The Relationship Between Fraud Pentagon, Audit Quality, and Financial Performance with the Risk of Financial Statement Fraud: An Empirical Study on PT Indofarma - Carsinah Azhara; Sirri Mubarokah; Cahya Dewi Kirani; Janiman Janiman (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to analyze the effect of Fraud Pentagon, Audit Quality, and Financial Performance on the risk of financial statement fraud at PT Indofarma Tbk during the period 2020-2023. The method used is a quantitative approach with a linear regression model, as well as fraud detection through the Beneish M-Score and evaluation of risk factors using the Fraud Pentagon Model. The results showed that the Beneish M-Score value was consistently above the -2.22 threshold, indicating the potential for earnings manipulation throughout the observation period, with the highest peak in 2022. In addition, the Fraud Pentagon Score increased significantly in 2023, mainly influenced by the pressure (1.00000) and competence (0.94069) factors, which are the main indicators of increased fraud risk. Although the regression test results show that the effect of the three variables is not statistically significant (p-value > 0.05), the Fraud Pentagon has the highest practical contribution (R² = 0.302) in explaining the variation of report manipulation. This finding confirms the importance of monitoring financial pressure and perpetrator competence in the early detection of fraud. This study recommends strengthening corporate governance, increasing auditor independence, and managing financial pressure as more effective fraud prevention strategies.